(3fXe GddBdi GdeHOYI aj UfYI GdcJGHI GdeNJQYIs - (3fLe GdOjf GdZRj , eMeO Hf eMeO Hf eMeO GdZRj GdYGeQj GdbQTj, fLe GdOjf CHh GdecGQe,J (B1061 (3g` s
(3ChdgG (B:s
(3bGd GdQVi GdMeO ddg ceG Yde HGdYde ef bO cQeG jHOC HHGH GdeeOhO s
(3BNQgG (B:s
(3hUMHg GdefJNHjf hGdSdGe hfSCd Gddg dfG MSf GdNJGe bdJ hHGdNjQ JeJ s
(3hgj CQLhRI ai GdUQas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B288s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B660s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3UQa JjehQ (B102) s
Keywords: (3GdUQas